Healing process of myocardial edema in acute perimyocarditis: Observation by speckle‐tracking echocardiography and cardiac magnetic resonance parametric mapping. Issue 1 (13th December 2022) - Adachi, Hidenori; Ihara, Madoka; Nojima, Yuhei; Nanto, Shinsuke
Abstract: This report describes the case of a 42‐year‐old male patient with acute viral perimyocarditis. The case study serves as a demonstration of the use of speckle‐tracking echocardiography and cardiac magnetic resonance (CMR) imaging in monitoring myocardial changes associated with perimyocarditis. It explores the possibility that regional longitudinal strain (LS) may predict prognosis in the affected areas of the myocardium, and could reflect more advanced areas of myocyte damage within myocardial edema.